Development of a deformation-based micro surface texturing system for friction reduction (part II) - Huang, Jia Zhao (2015)
Friction is a typical mode of failure which makes machine parts no longer function as intended. Surface texturing is one of the most effective friction reduction methods, which has been developing for decades and now plays an essential role in enhancing friction resistance of mechanical components. The friction reduction mechanism presented is based on the fact that both the lubricant retention and the debris entrapment can be achieved by creating micro reservoirs during the surface texturing process. There are many ways to manufacture micro-surface texture, among them, deformed-based micro-surface texturing is the least studied one whereas it has many unique advantages that cannot be surpassed by the rest, such as high production efficiency, high geometrical precision credibility and smooth surface finishing. This study aims at developing an economic micro embossing machine to commercially apply this technique. Besides, a new demonstrator for examining the friction reduction efficiency of the micro-surface texture is designed and built. A flat die with a dimple projection patterns is employed and the height of projection is set to 40 µm. The materials used are austenitic stainless steel, SUS303, 10±0.0005 mm. After the form-rolling, the machine is able to produce micro-surface texture with a fidelity of around 98%. An average angular offset of 5.16° exists which indicates an obtlateness within 20.26 µm for the embossment. The friction reduction efficiency test is conducted at a rotatory speed of 50 rpm with the lubricating oil SAE of 30 viscosity, the micro-surface texture is able to reach a 48.1% friction reduction efficiency when the average depth of formed grooves is around 29.4 µm.